PENGARUH PERTUMBUHAN EKONOMI DAN PENGANGGURAN TERHADAP KEMISKINAN DI KABUPATEN PANGKAJENE DAN KEPULAUAN. - Alfiyyah, Ashma Fiya; Damayanti, Alfina; Asdar, Asdar; Nasrullah, Nasrullah (Jurnal Ekonomi Sakti, 2025)
This study aims to determine the Effect of Economic Growth and Unemployment on Poverty in Pangkajene and Kepulauan Regency. The type of data used in this study is quantitative data obtained from time series data from 2014-2023. Data collection using observation and documentation methods. The data collected was processed using multiple linear regression analysis methods with the help of SPSS version 30. The results of this study indicate that: (1) Economic Growth does not have a significant effect on poverty in Pangkajene and Kepulauan Regency. This is evidenced by the variable coefficient of 0.076 with a significant value of 0.538 which is greater than 0,10 (0.538 > 0,10) also evidenced by the calculated t value which is smaller than the t table (0.647 <1.894). (2) Unemployment has a significant effect on poverty in Pangkajene and Kepulauan Regency. This is proven by the variable coefficient value of 0.571 with a significant value of less than 0,10 (0.64 < 0,10), also proven by the calculated t value which is greater than the t table (2.194 > 1.894). Keywords: Economic Growth, Unemployment and Poverty